Mechanisms of Fundamental Electromagnetic Wave Radiation in the Solar Wind - C. Krafft; P. Savoini; F. J. Polanco-Rodríguez (The Astrophysical Journal Letters, 2024)
Large-scale and long-term two-dimensional particle-in-cell simulations performed for parameters relevant to type III solar radio bursts have provided new results on the generation mechanisms of fundamental electromagnetic waves radiated at the plasma frequency ω _p . The paper first considers the nonlinear wave interaction process of electromagnetic decay (EMD) in a homogeneous solar wind plasma with an electron-to-ion temperature ratio T _e / T _i > 1. The dynamics of ion-acoustic waves (dispersion, spectra, growth/damping) is studied, and signatures confirming the three-wave interactions (cross-bicoherence, correlations between waves’ phases and between waves' growths, resonance conditions) are provided. The decisive role played in EMD by the backscattered Langmuir waves coming from the electrostatic decay (ESD) is demonstrated. EMD can be triggered by ion acoustic waves coming from the two cascades of the faster and more intense ESD. The same study is then performed in a solar wind plasma with random density fluctuations. In this case, EMD is not suppressed but develops only within plasma regions of reduced or quasi-uniform density. It coexists with linear mode conversion (LMC) of Langmuir waves into electromagnetic radiation, which is the fastest and most prominent process, as well as with ESD. LMC can lead to enhanced occurrence of EMD in the early stage. Moreover, the impact of T _e / T _i on electromagnetic energy growth and saturation is shown to be rather weak. Ion-acoustic waves are heavily damped at T _e ∼ T _i , so that EMD is overcome by nonlinear induced scattering on thermal ions. In actual solar wind plasmas, EMD should be more easily observed in plasma regions weakly perturbed by the background density turbulence and where ion temperature is decreased.